QUALITATIVE ANALOGY OF CUSTOMER SERVICE DELIVERY STRATEGIES ON CUSTOMER RELATIONSHIP DIMENSIONS: NIGERIAN INSURANCE INDUSTRY EXPERIENCE (Journal of the Management Sciences, 2025)
Given the sector's pervasive trust deficit, understanding how specific strategies like complaint handling and technical competence of the service staff regarding insurance products are very important. This exploratory, small-scale study investigated the relationship between customer service delivery strategies on customer relationship dimensions among customers of the selected insurance firms (AIICO Insurance Plc., Leadway Assurance Company Limited and FBNInsurance Limited) in Lagos State, Nigeria. Using a qualitative research design, the study conducted face-to-face interviews with four participants. The data, analyzed with NVivo software, revealed preliminary insights into how customer service delivery strategies influence customer relationship. The findings from the study’s thematic analysis suggest a potential link between a firm's customer service delivery strategies and customer relationship, based on the experiences shared by the six interviewees. The study's main takeaway is that prioritizing efficient and effective service delivery appears to be a factor in fostering customer satisfaction and loyalty. Based on these initial insights, we suggest that service providers consider focusing on customer service delivery programs to improve customer relationships and brand awareness. Imminent, larger-scale study would be helpful to additionally explore and confirm these foundational findings.
Keywords: : Complaint Handling; Customer Loyalty; Customer Satisfaction; Customer Service Delivery; Customer Relationship